A retrospective analysis of 3954 patients in phase 2/3 trials of bortezomib for the treatment of multiple myeloma: towards providing a benchmark for the cardiac safety profile of proteasome inhibition in multiple myeloma. (3rd May 2017) - Laubach, Jacob P.; Moslehi, Javid J.; Francis, Sanjeev A.; San Miguel, Jesús F.; Sonneveld, Pieter; Orlowski, Robert Z.; Moreau, Philippe; Rosiñol, Laura; Faber, Edward A.; Voorhees, Peter; Mateos, Maria‐Victoria; Marquez, Loreta; et al.
Summary: This retrospective analysis aimed to establish the overall cardiac safety profile of bortezomib using patient‐level data from one phase 2 and seven phase 3 studies in previously untreated and relapsed/refractory multiple myeloma (MM). Seven clinically relevant primary [congestive heart failure (CHF), arrhythmias, ischaemic heart disease (IHD), cardiac death] and secondary (hypertension, dyspnoea, oedema) cardiac endpoints were defined based on MedDRA v16.0 preferred terms. 2509 bortezomib‐treated patients and 1445 patients in non‐bortezomib‐based control arms were included. The incidence of grade ≥3 CHF was 1·3–4·0% in studies in relapsed/refractory MM and 1·2–4·7% in previously untreated MM (2·0–7·6% all grades), with no significant differences between bortezomib‐ and non‐bortezomib‐based arms in comparative studies. Incidences of arrhythmias (1·3–5·9% grade ≥2; 0·6–4·1% grade ≥3), IHD (1·2–2·9% all grades; 0·4–2·7% grade ≥3) and cardiac death (0–1·4%) were low, with no differences between bortezomib‐based and non‐bortezomib‐based arms. Higher rates of oedema (mostly grade 1/2) were seen in bortezomib‐based versus non‐bortezomib‐based arms in one study and a pooled transplant study analysis. Logistic regression analyses of comparative studies showed no impact on cardiac risk with bortezomib‐based versus non‐bortezomib‐based treatment. Bortezomib‐based treatment was associated with low incidences of cardiac events.